2021
DOI: 10.1002/onco.13715
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ado-Trastuzumab Emtansine and Fam-Trastuzumab Deruxtecan on Metastatic Breast Cancer Harboring HER2 Amplification and the L755S Mutation

Abstract: Somatic mutations in human epidermal growth factor receptor 2 (HER2) are present in approximately 3% of breast cancers. Some HER2 mutations are activating, and they represent a mechanism of resistance to conventional anti-HER2 therapies such as trastuzumab and lapatinib. Consistently, in patients with HER2-amplified breast cancer, these mutations are predominantly observed in metastatic tumors obtained after exposure to anti-HER2 systemic therapies, possibly after clonal selection. Therefore, it is rare to fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…The development of new targeted therapies, such as aromatase inhibitors, monoclonal antibodies (trastuzumab, pertuzumab, T-DM1), and lapatinib, has improved remarkably the outcome for endocrine-sensitive or HER2-positive breast cancer subtypes ( Giordano et al, 2004 ). Some interesting developments resulted in further improvement of these agents, such as creation of clinically approved trastuzumab-based antibody-drug conjugates (Ado-Trastuzumab Emtansine and Fam-Trastuzumab Deruxtecan) ( Mukohara et al, 2021 ). Additionally, HER2-positive tumors respond well to several clinically approved tyrosine kinase inhibitors ( Schlam and Swain, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The development of new targeted therapies, such as aromatase inhibitors, monoclonal antibodies (trastuzumab, pertuzumab, T-DM1), and lapatinib, has improved remarkably the outcome for endocrine-sensitive or HER2-positive breast cancer subtypes ( Giordano et al, 2004 ). Some interesting developments resulted in further improvement of these agents, such as creation of clinically approved trastuzumab-based antibody-drug conjugates (Ado-Trastuzumab Emtansine and Fam-Trastuzumab Deruxtecan) ( Mukohara et al, 2021 ). Additionally, HER2-positive tumors respond well to several clinically approved tyrosine kinase inhibitors ( Schlam and Swain, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… 41 Mukohara et al reported a case of BC with HER2 amplification and L755S mutation in which the patients exhibited an excellent response to T-DXd, after initial progression with trastuzumab and lapatinib therapy. 42 Both T-DM1 and T-DXd have been demonstrated to be promising agents for the treatment of lung cancer with HER2 mutations. 22 , 42 At present, the potential of these ADCs for the treatment of HER2 -mutated metastatic BC is unclear, but there is an ongoing clinical trial on the efficacy of T-DXd for the treatment of HER2 -mutated BC (NCT04639219).…”
Section: Discussionmentioning
confidence: 99%
“…mPFS was 8.2 months and median overall survival was 17.8 months. Mukohara et al 62 reported a breast cancer case with both HER2 amplification and the L755S mutation showing excellent responses to T-DM1 and then T-DXd after progression on trastuzumab and lapatinib.…”
Section: Discussionmentioning
confidence: 99%